Percepção de alunos do 2° ano do Ensino Médio sobre animais peçonhentos, em uma escola pública do município de Santarém no Pará - (:unkn) unknown (UNIVERSIDADE FEDERAL DO OESTE DO PARÁ, 2024)
Venomous animals use an organ in their body to inject poison into their victims. They are called venomous animals, which, in order to hunt or defend themselves, have the ability to inoculate toxic substances (venom) produced in specialized glands in their bodies, thus recording popular knowledge, as well as beliefs regarding these animals. The present work aims to investigate the level of clarification about venomous animals in a 2nd year high school class at a public school in Santarém through interviews with open and closed questions containing 11 questions. We saw that the majority of those interviewed still have little knowledge about venomous animals and do not know how to distinguish a venomous animal from a poisonous animal and, due to lack of this knowledge, they end up eliminating several animals that are not dangerous. Among the most cited animals are venomous animals: snakes, centipedes and spiders and those that cause the most accidents are snakes. After collecting the data, we carried out an intervention so that students could better understand the topic through bibliographical research in the school's computer laboratory and a visit to the Ufopa Biology laboratory, which allowed them to observe venomous animals and learn about their characteristics. of them and their role in ecology providing them with a more affective understanding of the subject. After these activities, the students presented their work at the school science fair. We concluded that the prior diagnosis of the students' level of knowledge was extremely important to guide teaching practice, in order to complement or demystify the concepts they had, and we saw that the interaction of the school/university and through internet research, and Through public exhibitions, students had to make sure they correctly understood the terms to explain to the fair's audience. This research showed that we can add several methodologies to improve biology teaching on biodiversity and animal conservation in public schools.
Keywords: Animais peçonhentos; Animal venenoso; Ecologia – Ensino Médio; Estudantes do Ensino Médio; CNPQ:: CIÊNCIAS BIOLÓGICAS